The ideological endeavors of the Alianza de Intelectuales Antifranquistas during the Republican exile: the writings of María Teresa León in Argentine journal Saber Vivir (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
During her long exile in Argentina, María Teresa León carried on a prolific intellectual and creative career, much of it related to the intellectual and editorial network of the Republican exile. In this paper, I analyze her writings published in the journal Saber Vivir, edited in Buenos Aires between August 1941 and November 1956, shedding light to a production that has been little explored by the critics. In Saber Vivir, the authoress published essays on art and literature, pieces of literary creations and cultural reviews on Spanish life and traditions. I will comment on some of her contributions, considering how in those writing León redesigns the creative project of the Alianza de Intelectuales Antifascistas (Antifascist Intellectual Alliance) and how, in them, politics replaces political struggles. In that process, poetic language, philologic and erudite knowledge (particularly on Spanish literature and culture) are keynotes. Also, an acute consciousness of sexual difference and inequalities is visible in this production. In doing so, I intend to contribute to the understanding of María Teresa León’s originality within the context of the Republican exile.
Keywords: Republican Exile; María Teresa León; Journalistic Writings; Journal Saber vivir; Antifascism